Parallel DNA/RNA NGS Using an Identical Target Enrichment Panel in the Analysis of Hereditary Cancer Predisposition - Kleiblová, Petra; Černá, Marta; Zemánková, Petra; Matějková, Kateřina; Nehasil, Petr; Hojný, Jan; Horáčková, Klára; Janatová, Markéta; Soukupová, Jana; Šťastná, Barbora; Kleibl, Zdeněk (Folia biologica, 2024)
Germline DNA testing using the next-gene-ration sequencing (NGS) technology has become the analytical standard for the diagnostics of hereditary diseases, including cancer. Its increasing use places high demands on correct sample identification, independent confirmation of prioritized variants, and their functional and clinical interpretation. To streamline these processes, we introduced parallel DNA and RNA capture-based NGS using identical capture panel CZECANCA, which is routinely used for DNA analysis of hereditary cancer predisposition. Here, we present the analytical workflow for RNA sample processing and its analytical and diagnostic performance. Parallel DNA/RNA analysis allowed credible sample identification by calculating the kinship coefficient. The RNA capture-based approach enriched transcriptional targets for the majority of clinically relevant cancer predisposition genes to a degree that allowed analysis of the effect of identified DNA variants on mRNA processing. By comparing the panel and whole-exome RNA enrichment, we demonstrated that the tissue-specific gene expression pattern is independent of the capture panel. Moreover, technical replicates confirmed high reproducibility of the tested RNA analysis. We concluded that parallel DNA/RNA NGS using the identical gene panel is a robust and cost-effective diagnostic strategy. In our setting, it allows routine analysis of 48 DNA/RNA pairs using NextSeq 500/550 Mid Output Kit v2.5 (150 cycles) in a single run with sufficient coverage to analyse 226 cancer predisposition and candidate ge-nes. This approach can replace laborious Sanger confirmatory sequencing, increase testing turnaround, reduce analysis costs, and improve interpretation of the impact of variants by analysing their effect on mRNA processing.
Keywords: High-Throughput Nucleotide Sequencing; Neoplasms; Sequence Analysis, DNA; nádory; Reproducibility of Results; sekvenční analýza RNA; DNA; lidé; reprodukovatelnost výsledků; sekvenční analýza DNA; Sequence Analysis, RNA; RNA; genetická predispozice k nemoci; vysoce účinné nukleotidové sekvenování; Genetic Predisposition to Disease; Humans